Efficiency of thermomechanical reclaiming of ground tire rubber conducted in counter-rotating and co-rotating twin screw extruder - Formela, K.; Cysewska, M (Polimery, 2014)
In this article the results of research on a continuous thermomechanical reclaiming process of ground tire rubber (GTR) conducted in a twin screw extruder are presented. The effects of the rotation direction (co-rotating/counter-rotating), design of co-rotating plasticizing units and the rotational speed of the screws on the extruder working parameters, sol fraction and the degree of reclaiming in the obtained products were described. The influence of secondary vulcanization on cure characteristics as well as mechanical properties of revulcanizates, and blends of reclaimed rubber and styrene-butadiene rubber (SBR) were determined. Based on the obtained results, it was concluded that the application of counter-rotating plasticizing system (i.e. screw profile A), consisting mainly of transport elements with different pitch, increases the time during which ground tire rubber is exposed to the barrel temperature. The use of co-rotating plasticizing system, equipped with kneading elements and characterized by constant pitch, causes that the retention time of ground tire rubber in the extruder barrel is much shorter. In the case of co-rotating plasticizing system, it is also higher shear forces (then in counter-rotating screw configuration), besides temperature, acts on ground tire rubber, and converts mechanical energy into heat. Testing of styrene-butadiene rubber-ground tire rubber/reclaimed ground tire rubber (SBR-GTR/dGTR) compounds confirmed that the reclaiming process has positive influence on properties of obtained products.